2022
DOI: 10.1590/1519-6984.265069
|View full text |Cite
|
Sign up to set email alerts
|

Methods of application of salicylic acid as attenuator of salt stress in cherry tomato

Abstract: Salt stress caused by excess salts present in irrigation water, is one of the biggest barriers in agricultural production, especially in semi-arid regions. Thus, the use of substances, such as salicylic acid, that minimize the deleterious effects of salinity on plants can be an alternative to ensure satisfactory production. In this context, the objective of this study was to evaluate the effects of different methods of application of salicylic acid on the growth, production and water use efficiency of cherry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The increase in the number of fruits observed in the present study could be related to the eliciting role of salicylic acid, inducing an increase in photosynthetic activity and improving the translocation of photoassimilates for fruit production (Diaz et al, 2016). Similar results were obtained by Silva et al (2022b) with cherry tomato under different application methods of salicylic acid irrigated with saline waters (ECw ranging from 0.6 to 2.6 dS m -1 ), reaching the highest value for the number of fruits (37 fruits per plant) under foliar application of salicylic acid (1 mM) and the ECw of 0.6 dS m -1 , corresponding to an increase of 42.31% (11 fruits per plant) compared to the control irrigated with the same salinity.…”
Section: Sources Of Variation Dfsupporting
confidence: 86%
See 2 more Smart Citations
“…The increase in the number of fruits observed in the present study could be related to the eliciting role of salicylic acid, inducing an increase in photosynthetic activity and improving the translocation of photoassimilates for fruit production (Diaz et al, 2016). Similar results were obtained by Silva et al (2022b) with cherry tomato under different application methods of salicylic acid irrigated with saline waters (ECw ranging from 0.6 to 2.6 dS m -1 ), reaching the highest value for the number of fruits (37 fruits per plant) under foliar application of salicylic acid (1 mM) and the ECw of 0.6 dS m -1 , corresponding to an increase of 42.31% (11 fruits per plant) compared to the control irrigated with the same salinity.…”
Section: Sources Of Variation Dfsupporting
confidence: 86%
“…Salicylic acid is involved in plant growth and in physiological processes such as floral induction, stomatal regulation, ion absorption, photosynthesis, and respiration by intensifying the activity of antioxidant enzymes and providing protection against membrane damage (Silva et al, 2020;Esan et al, 2017). Studies have reported that the application of salicylic acid can mitigate the deleterious effects of salt stress in various vegetable crops, as observed in tomato (Silva et al, 2022b), basil (Silva et al, 2022c) and even bell pepper (Veloso et al, 2021). However, such studies have been limited to investigating concentrations and application methods, with no reports regarding the frequency of application of salicylic acid, especially in bell pepper.…”
Section: Setting Up and Conduction Of The Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polar (Figure 5A) and equatorial (Figure 5B) diameters of cherry tomatoes were negatively affected by the increase in electrical conductivity of the nutrient solution. Silva et al [1], when evaluating the growth and production of cherry tomatoes under salt stress (ECw ranging from 0.6 to 2.6 dS m −1 ) in conventional cultivation, observed reductions of 4.54% in FPD and 2.52% in FED when comparing plants irrigated with the highest salinity (2.6 dS m −1 ) to those cultivated with ECw of 0.6 dS m −1 . Excess salts present in the nutrient solution cause osmotic stress, negatively affecting the absorption of water and nutrients by plants [44], which may have resulted in reductions in FPD and FED observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Cherry tomato (Solanum lycopersicum L.) is among the principal vegetables most cultivated in protected environments [1]. In recent years, its cultivation has increased worldwide, especially due to the added economic value and nutritional benefits [2].…”
Section: Introductionmentioning
confidence: 99%